(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article explores the challenges and issues associated with increasing the innovative professional training of future primary school teachers. It discusses various methods employed in such training, presents the results of these efforts, engages in a critical discussion of the findings, and concludes with suggestions for improvement